Evidence of a Monoclonal Origin for Bilateral Serous Tubal Intraepithelial Neoplasia. (September 2019) - Meserve, Emily E.; Strickland, Kyle C.; Miron, Alexander; Soong, Thing R.; Campbell, Frank; Howitt, Brooke E.; Crum, Christopher P.
Abstract : Serous tubal intraepithelial carcinoma (STIC) is found in 10% to 60% of cases of tuboovarian high-grade serous carcinoma (HGSC) and is presumed to be the site of origin, linking many HGSCs to the fallopian tube. Bilateral STIC is present in ∼20% of cases. Because clonal Tp53 mutations are a defining feature of HGSC, including their associated STICs, we analyzed 4 cases of bilateral serous tubal intraepithelial neoplasia (STIN), including STIC and Tp53 -mutated serous tubal intraepithelial lesions (STILs), associated with HGSC to determine whether they contained the same or different p53 mutations. Extracted DNA from STINs, concurrent HGSCs and control tissues was analyzed for mutations in all exons of Tp53 . Sequencing was successful in 3 of the 4 cases, and an identical Tp53 mutation was detected in the HGSC and bilateral STINs in 2 of these 3 cases. One STIN was morphologically a STIL. These findings confirm that a subset of bilateral STINs share the same Tp53 mutation, implying that at least one of the STINs is an intraepithelial metastasis from either the contralateral STIN or HGSC. This study complements others addressing the multiple origins of STIN in the setting of existing HGSC. It further underscores the fact that potential overlap in biologic behavior between STILs and STICs as well as timing and direction of metastatic spread has yet to be resolved.